Spin alignment of ρ0 mesons produced in antineutrino and neutrino neon charged-current interactions - Wittek, W; Guy, J; Adeholz, M; Allport, P; Baton, J; Berggren, M; Bertrand, D; Brisson, V; Bullock, F; Burkot, W; Calicchio, M; Clayton, E; et al. (1987)
In a bubble chamber experiment with BEBC the spin alignment parameter η= 1 2 (2ρ{variant}00 - ρ{variant}11 - ρ{variant}-1-1) is measured for ρ{variant}0 mesons produced in deep inelastic charged-current antineutrino and neutrono interactions on neon. In the current fragmentation region η is found to be ηv=0.48±0.27 (stat.)±0.15 (syst.) for vNe and ηv=0.12±0.20 (stat.)±0.10 (syst.) for vNe interactions. © 1987.